2012
DOI: 10.1371/journal.pone.0035740
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1-Dependent Endothelial Cell Death Determines Severity of Radiation-Induced Intestinal Injury

Abstract: Normal tissue toxicity still remains a dose-limiting factor in clinical radiation therapy. Recently, plasminogen activator inhibitor type 1 (SERPINE1/PAI-1) was reported as an essential mediator of late radiation-induced intestinal injury. However, it is not clear whether PAI-1 plays a role in acute radiation-induced intestinal damage and we hypothesized that PAI-1 may play a role in the endothelium radiosensitivity. In vivo, in a model of radiation enteropathy in PAI-1 −/− mice, apoptosis of radiosensitive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…Immunohistochemistry combined with flow cytometric analysis showed a major infiltration of macrophages into the colonic mucosa and submucosa 7 days after irradiation, particularly at 20 Gy. The dose-dependant microvasculature apoptosis induced by irradiation may contribute to alter the transendothelial migration and in fine the monocytes-macrophages recruitment notably at the high dose of 27 Gy (Abderrahmani et al, 2012). Immunophenotyping demonstrated that these macrophages expressed TLR4 and TLR5 and that these specific TLR4 1 and TLR5 1 macrophage subsets were most frequent after irradiation.…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemistry combined with flow cytometric analysis showed a major infiltration of macrophages into the colonic mucosa and submucosa 7 days after irradiation, particularly at 20 Gy. The dose-dependant microvasculature apoptosis induced by irradiation may contribute to alter the transendothelial migration and in fine the monocytes-macrophages recruitment notably at the high dose of 27 Gy (Abderrahmani et al, 2012). Immunophenotyping demonstrated that these macrophages expressed TLR4 and TLR5 and that these specific TLR4 1 and TLR5 1 macrophage subsets were most frequent after irradiation.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Serpine1 regulates endothelial cell proliferation (Ploplis et al, 2004), apoptosis (Balsara and Ploplis, 2008;Abderrahmani et al, 2012) and migration (Isogai et al, 2001) and is upregulated in the injured neonatal heart (Darehzereshki et al, 2015).…”
Section: Notch Signalling Regulates Cardiomyocyte Proliferation and Dmentioning
confidence: 99%
“…They acquire SASP by expressing increased levels of inflammatory cytokines and adhesion molecules (15, 18, 25, 26, 57, 77, 79). Radiation-induced senescent endothelial cells expressed decreased levels of thrombomodulin (80, 81) and increased levels of plasminogen activator inhibitor-1 (PAI-1) (82, 83). All these changes in senescent endothelial cells lead to endothelial dysfunction, which results in inhibition of angiogenesis, induction of oxidative stress and inflammation and dysregulation of vasodilation and hemostasis.…”
Section: Endothelial Cell Senescence Induced By Ionizing Radiationmentioning
confidence: 99%